Infographics : the power of visual storytelling - Lankow, Jason; Ritchie, Josh; Crooks, Ross (John Wiley & Sons, Inc., 2012)
Transform your marketing efforts through the power of visual content In today's fast-paced environment, you must communicate your message in a concise and engaging way that sets it apart from the noise. Visual content - such as infographics and data visualization - can accomplish this. With DIY functionality, The Power of Infographics will teach you how to find stories in your data, and how to visually communicate and share them with your audience for maximum impact. The Power of Infographics will show you the vast potential to using the communication medium as a marketing tool by ...